PENERAPAN KONSELING MENGGUNAKAN TEKNIK PERSON CENTERED THERAPY (PCT) DALAM KASUS PENYIMPANGAN SEKSUAL - Falisa Oktafiani; Nadya Indria Wandari; Candara Aulia Nafisah; Intan Nur Fadhilla; Oetari Zakiyah Aji; Muhamad Afifuddin Ghozali (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The problem discussed in this research is sexual deviation in the form of LGBT which is caused by sexual violence. The purpose of this research is to explore the application of Person-Centered Therapy (PCT) in helping individuals get out of this situation. This research uses a qualitative approach with a case study method. The research subject is an individual who experiences sexual deviation. Data was collected through interviews and observations with certain guidelines, and analyzed using qualitative descriptive analysis. The research results show that the Person-Centered Therapy (PCT) technique is effective in helping clients recognize behavior that is considered wrong and the factors that influence it, because this approach is towards unconditional acceptance.